Postprocedure Mapping of Cardiac Resynchronization Lead Position Using Standard Fluoroscopy Systems: Implications for the Nonresponder with Scar. - Parker, Katherine M.; Bunting, Ethan; Malhotra, Rohit; Clarke, Samantha A.; Mason, Pamela; Darby, Andrew E.; Kramer, Christopher M.; Salerno, Michael; Holmes, Jeffrey W.; Bilchick, Kenneth C. (Pacing & Clinical Electrophysiology, 2014)
Background The relationship between cardiac resynchronization therapy (CRT), left ventricular (LV) lead position, scar, and regional mechanical function influences CRT response. Objective To determine LV lead position relative to LV structural characteristics in standard clinical practice, we developed and validated a practical yet mathematically rigorous method to register procedural fluoroscopic LV lead position with pre-CRT cardiac magnetic resonance (CMR). Methods After one-time calibration of the standard fluoroscopic suite, we identified the projected CMR LV lead position using three reference landmarks on both CMR and fluoroscopy. This predicted lead position was validated in a canine model by histology and in eight 'validation group' patients based on postoperative computed tomography scans (n = 7) or CMR coronary sinus venography (n = 1). The methodology was applied in an additional eight patients with CRT nonresponse and infarction-related myocardial scar. Results The projected and actual lead positions were within 1.2 mm in the canine model. The median distance between projected and actual lead positions for the validation group (n = 8) and animal validation case was 11.3 mm (interquartile range 9.2-14.6 mm). In the application (nonresponder) group (n = 8), the lead mapped to the scar periphery in three patients, the core of the scar in one patient, and more than 3 cm from scar in four patients. Conclusions This methodology projects procedural fluoroscopic LV lead position onto pre-CRT CMR using standard fluoroscopic equipment and a one-time calibration, enabling assessment of LV lead position with sufficient accuracy to identify the lead position relative to regional function and infarction-related scar in CRT nonresponders.